Diseño de una planta piloto para la obtención de biodiesel de borra de café (2021)
With the aim of designing a biodiesel pilot plant from coffee grounds and making use of this residue in a new alternative; Initially, a series of bibliographic investigations of the use of coffee grounds in the production of biodiesel is carried out, finding results in the different methods for the extraction of the oil and its transesterification. When obtaining through the bibliography data such as the operating conditions, the process stages, the solvents to be used, among others, a matrix was made to select the method of both processes; resulting in the supercritical fluid method for both oil extraction and transesterification. The next steps were to carry out the study at a geographical level of the implementation of the pilot plant through different factors that determined the viability of applying the pilot plant in Colombia; On the other hand, the simulation of the biodiesel production process was carried out under supercritical conditions using data based on experimental systems from bibliographic searches.